패션 온라인 커뮤니티 특성이 브랜드 충성도에 미치는 영향: 라이프스타일 집단 간 비교 - 고은주; 권준희; 김경훈 (Journal of global scholars of marketing science, 2006)
인터넷의 보급과 함께 기업의 마케팅 도구로서 온라인 커뮤니티가 등장하였으며 최근 그 중요성이 점차 증가되고 있다. 패션 기업에서도 적은 비용으로 고객과 관계를 형성하여 궁극적으로 고객 충성도를 제고 할 수 있는 방안이라는 측면에서 온라인 커뮤니티에 주목하고 있다. 본 연구의 목적은 1) 패션 온라인 커뮤니티의 특성을 분석하고 2) 라이프스타일에 따라 세분화된 집단 유형별로 브랜드 충성도에 미치는 커뮤니티 특성 차이를 규명함으로써 라이프스타일 집단에 따른 효율적인 온라인 커뮤니티 마케팅 전략을 제안하고자 한다. 본 연구의 결과를 요약하면, 첫째, 패션 온라인 커뮤니티에서 제공되는 특성은 ``상호작용성``, ``정보제공성``, ``흥미제공성`` 3개의 요인으로 나타났다. 둘째, 라이프스타일에 따라 집단을 세분화한 결과 ``무관심형``, ``감각추구형``, ``합리추구형``의 3집단으로 구분되었으며, 라이프스타일 집단에 따라 온라인 커뮤니티특성이 브랜드 충성도에 미치는 영향 요인의 차이를 분석한 결과, 무관심형 집단은 커뮤니티의 상호작용성이, 감각추구형 집단은 정보제공성이, 합리추구형 집단은 흥미제공성과 정보제공성이 브랜드 충성도를 높이는 중요한 요인으로 나타났다. 본 연구는 패션 온라인 커뮤니티 회원들의 커뮤니티 이용 특성을 분석 함으로서 궁극적으로 패션 기업의 온라인 커뮤니티 전략 수립에 필요한 기초정보를 제시하였다. Importance of on-line community has been increased and also on-line community has been used as an important marketing tool. Fashion companies also considered that on-line community provides opportunities to develop customer relationship and to improve customer loyalty. The purpose of this study is 1) to identify the characteristics of fashion on-line community, 2) to investigate the differences of factors affecting brand loyalty among fashion lifestyle groups. For data collection, on-line survey was conducted for fashion on-line community members in Daum portal site and total 404 subjects were used for this study. Factor analysis, cluster analysis, and regression analysis were used for data analysis. The results of this study were as follow: first, characteristics of fashion on-line community were classified as three factors: ``interactivity``, ``information provision`` and ``interest provision``. Second, the impact of fashion on-line community characteristics on brand loyalty were found to be significantly different among lifestyle groups. The results from this empirical study provide basic information for strategic planning about on-line community by analyzing characteristics of on-line community users.